Screaming for Champions - Carroll, Jane (My University, 2022)
This short piece reflects on screaming and female rage in response to pregnancy and childbirth during the COVID-19 pandemic. This piece reflects on my daughter's expert screaming and my own (wasted) efforts trying to pacify her and get her to stop screaming.
The Banshee: The Leading Journal for Women who Scream
This short piece reflects on screaming and female rage in response to pregnancy and childbirth during the COVID-19 pandemic. This piece reflects on my daughter's expert screaming and my own (wasted) efforts trying to pacify her and get her to stop screaming.
Keywords: creative writing, creative non-fiction, motherhood, postpartum; Creative Arts Practice; Creative Writing